Mental and physical training with meditation and aerobic exercise improved mental health and well-being in teachers during the COVID-19 pandemic - Demmin, Docia L.; Silverstein, Steven M.; Shors, Tracey J. (Frontiers in Human Neuroscience, 2022)
Teachers face significant stressors in relation to their work, placing them at increased risk for burnout and attrition. The COVID-19 pandemic has brought about additional challenges, resulting in an even greater burden. Thus, strategies for reducing stress that can be delivered virtually are likely to benefit this population. Mental and Physical (MAP) Training combines meditation with aerobic exercise and has resulted in positive mental and physical health outcomes in both clinical and subclinical populations. The aim of this pilot study was to evaluate the feasibility and potential effectiveness of virtual MAP Training on reducing stress and improving mood and well-being in teachers. Participants (n = 104) were from recruited online from kindergarten-grade twelve (K-12) schools in the Northeastern region of the United States and randomly assigned to a six-week program of (n = 58) virtual MAP Training or no training (n = 13). Primary outcomes included pre-intervention and post-intervention ratings on self-report measures of social and emotional health. Changes in cognitive functioning and physical health were also examined in secondary analyses. By intervention end, participants in the MAP Training group reported less anxiety and work-related stress compared to those who received no training (ds = -.75- -.78). Additionally, MAP Training participants reported improvements in depressive symptoms, rumination, work-related quality of life, perceived stress, and self-compassion (ds = .38- -.82), whereas no changes were observed in the no training group. Participants also reported increased subjective ratings of executive functioning, working memory, cognitive flexibility, and fewer sleep disturbances (ds = -.41-.74). Together, these results suggest that the combination of meditation and aerobic exercise is an effective virtual intervention for improving mental health and well-being among K-12 teachers and may enhance resilience to stressful life events such as occurred during the coronavirus pandemic.